Commercialization of Publicly Funded Research and Development in Russia : Scaling up the Emergence of Spinoff Companies - Gutierrez, Juan Julio; Correa, Paulo (World Bank, Washington, DC, 2014)
This paper explores fundamental issues affecting technology commercialization of publicly funded research and development (R&D) in the Russian Federation. Despite substantial R&D investments, Russia has experienced a decline in scientific output and employment. Nevertheless, the innovation system remains strong in several technological fields. This paper develops an analytical framework to discuss conditions for technology commercialization, which hinge on the innovation system research base, governance of research institutions, alignment between specialization and sector prioritization, availability and performance of scientists and engineers, intellectual property (IP) regime for publicly funded discoveries, and early stage finance. The paper identifies areas for policy and regulatory improvement to incentivize research institutes and scientists to undertake research with market potential. These include: stronger results-based management that rewards commercialization efforts and focuses not only on high-technology sectors, but also on sectors where Russia has technological comparative advantages. In addition, researchers' career development could consider performance metrics that include entrepreneurial achievements, as well as support for young scientists and for international collaboration. Moreover, the IP regime for federally funded R&D may consider transferring full ownership of research discoveries to research organizations. Finally, to increase deal-flow of new ventures, enhancing the supply of early-stage financing for new technologies may be considered.